Accretion in action: phase space coherence of stellar debris and globular clusters in Andromeda's South-West Cloud - Mackey, Dougal; Huxor, Avon P. (Monthly notices of the Royal Astronomical Society. Letters, 2014)
A central tenet of the current cosmological paradigm is that galaxies grow over time through the accretion of smaller systems. Here, we present new kinematic measurements near the centre of one of the densest pronounced substructures, the South-West Cloud, in the outer halo of our nearest giant neighbour, the Andromeda galaxy. These observations reveal that the kinematic properties of this region of the South-West Cloud are consistent with those of PA-8, a globular cluster previously shown to be co-spatial with the stellar substructure. In this sense, the situation is reminiscent of the handful of globular clusters that sit near the heart of the Sagittarius dwarf galaxy, a system that is currently being accreted into the Milky Way, conﬁrming that accretion deposits not only stars but also globular clusters into the haloes of large galaxies.
Gesehen am 14.07.2020